Methodology Of Using Different Social Forms in Foreign Language Lessons (Eurasian Journal of Humanities and Social Sciences, 2021)
This article examines the methodology of using various social forms in foreign language classes, in particular, such as individual work, work in pairs, in a small group, frontal work, and teamwork.